Family firms and regional context: literature overview, agenda framing and future research directions - Evans Korang Adjei; Stefano Amato; Rodrigo Basco; Lech Suwala (Review of Regional Research, 2025)
Recently family firms seen a~delicate renewed interest in regional science, regional studies and economic geography and similarly, spatial and regional contexts have been addressed in family business studies. Those strands are driven by interest in the heterogeneity of family firms as the most common type of organization all over the world (family spatialities) and the heterogeneity of spatial and regional context as a~significant selection filter for the behavior and performance of family firms (spatial familiness). This editorial addresses these unique settings of family firms and the nature of spatial/regional contexts in a~greater depth, by providing a~concise literature overview on contextualizing research, by presenting a~star shaped model to systemize research around spatial and regional contexts, and by suggesting further research directions. Our proposed star-shaped model frames a~holistic view on spatial and regional contexts though a scientific agenda that differentiates between theoretical explanations and modelling ( spatial concepts ), empirical descriptions and analyses ( spatial factors, spatial structures, spatial settings ), and policy recommendations ( spatial policies ). These elements are shaped by scalar ( spatial frames ) and temporal frames ( spatial processes ). Most of these spatial building blocks and their interplay are explored by the articles in this special issue.
Keywords: 910; Family firms; Spatial/regional context; Spatial familiness; Family spatialities